Pengaruh Nilai-Nilai Sosial, Pertimbangan Pasar Kerja Dan Pengakuan Profesional Terhadap Minat Mahasiswa Akuntansi Menjadi Akuntan Publik (Studi Kasus pada Mahasiswa Akuntansi Angkatan 2020 UNISBAR) - Sulastri, Sulastri; Fathiah, Fathiah; Mukhtar, Akasby (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to determine the effect of social values, labor market considerations and professional recognition on partially and simultaneously the interest of accounting students to become public accountants in Accounting Students class of 2020 at the University of West Sumatra. This type of research is quantitative with associative methods. The population in this study were accounting students at the University of West Sumatra in the 2020 class of 50 people. Withdrawal of samples using the total sampling method, the number of samples used as many as 50 respondents. Data collection techniques used questionnaires, while data analysis methods used validity and reliability tests, descriptive statistics, classical assumptions (normality test, multicollinearity test and heteroscedasticity test), multiple linear regression analysis, and statistical tests (t test, F test and coefficient of determination).The results showed that the social values ​​variable had no effect and was not significant on the interest of accounting students to become public accountants with a tcount of -0.999 < ttable 1.675 at a significant level of 0.323 > 0.05, the labor market considerations variable had a significant effect on interest in accounting students to become a public accountant with a t-value of 4.601 > t-table 1.675 at a significant level of 0.000 <0.05, the professional recognition variable is influential and significant to the interest of accounting students to become a public accountant with a t-count of 3.096 > t-table 1.675 at a significant level of 0.004 <0, 05 and the variable social values, labor market considerations and professional recognition simultaneously have a significant effect on the dependent variable the interest of accounting students to become public accountants with a value of Fcount = 35.058 > Ftable 2.56 with sig = 0.000 <0.05.